Kualitas Kepemimpinan Guest Service Centre Supervisor Pada Masa Pandemi Covid-19 Di Padma Resort Legian - Ni Komang Widiastari; I Wayan Seniartha; I Gusti Ayu Putu Wita Indrayani (Program Studi Manajemen Divisi Kamar, 2022)
This writing aims to determine the leadership quality of the Guest Service Center Supervisor during the Covid-19 Pandemic at Padma Resort Legian. Data obtained by interview and questionnaire techniques. Data analysis in this study is descriptive qualitative. In this paper, the data obtained are as follows: the results of a questionnaire regarding the leadership quality of the guest service center supervisor during the COVID-19 pandemic at Padma Resort Legian. There are ten dimensions to measure the leadership quality of the guest service center supervisor during the COVID-19 pandemic at Padma Resort Legian. From the results of the discussion, it can be seen that the dimension